Common errors in reporting cause-of-death statement on death certificates: A systematic review and meta-analysis - Alipour, Jahanpour; Payandeh, Abolfazl (Journal of forensic and legal medicine, 2021)
The prevalence of death certificate (DC) completion errors is a universal issue. This research aimed to estimate the global prevalence of DC errors by performing a systematic review and meta-analysis. Databases including Web of Science, PubMed, Science Direct, Scopus, and Google search engine were searched by September 4, 2020. Thirty-five articles were included in the final analysis. The exact Clopper–Pearson confidence intervals, heterogeneity assessment, random effects models with Mantel-Haenszel methods were employed using STATA version 14.2 software. Absence of time interval (80.9%), absence/inappropriateness of comorbidities (45.1%), incorrect underlying cause-of-death (COD) statement (38.9%), improper sequence (36.2%), mechanism of death with underlying COD (UCOD) (33.6%), abbreviations (33.0%), mechanism only (23.9%), competing causes (21.5%), two or more condition per line (19.3%), incorrect COD (18.0%), nonspecific or ill-defined condition (16.4%), blanks/repetitive phrases (12.5%), and illegible handwriting (11.6%) were the most prevalent errors, respectively. Lack of or poor training/educating of certifiers, lack of physician understandings about the importance of DC and absence of quality assurance mechanisms were identified as the most significant causes of DC errors. Furthermore, providing ongoing, targeted and interactive training/education, and establishment of quality control and tracking mechanisms for completion of deficient DCs were suggested as the important improving solutions.